2021
DOI: 10.1038/s42003-021-02280-1
|View full text |Cite
|
Sign up to set email alerts
|

The γ-tubulin meshwork assists in the recruitment of PCNA to chromatin in mammalian cells

Abstract: Changes in the location of γ-tubulin ensure cell survival and preserve genome integrity. We investigated whether the nuclear accumulation of γ-tubulin facilitates the transport of proliferating cell nuclear antigen (PCNA) between the cytosolic and the nuclear compartment in mammalian cells. We found that the γ-tubulin meshwork assists in the recruitment of PCNA to chromatin. Also, decreased levels of γ-tubulin reduce the nuclear pool of PCNA. In addition, the γ-tubulin C terminus encodes a PCNA-interacting pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…It has been reported that γ-tubulin binds PCNA and aids in its recruitment to chromatin in mammalian cells. A positive correlation between γ-tubulin and PCNA expression was found in all examined tumor types (Corvaisier et al, 2021). Finally, γ-tubulin is capable to modulate the anaphase-promoting complex/cyclosome (APC/C), which is a large protein complex with multiple subunits that is important for cell cycle regulation.…”
Section: γ-Tubulin Nuclear Functionsmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been reported that γ-tubulin binds PCNA and aids in its recruitment to chromatin in mammalian cells. A positive correlation between γ-tubulin and PCNA expression was found in all examined tumor types (Corvaisier et al, 2021). Finally, γ-tubulin is capable to modulate the anaphase-promoting complex/cyclosome (APC/C), which is a large protein complex with multiple subunits that is important for cell cycle regulation.…”
Section: γ-Tubulin Nuclear Functionsmentioning
confidence: 88%
“…As described in the following section, γ-tubulin can also be found in cell nuclei. It has been proposed that γ-tubulin filaments may also play a structural role in nuclei (Corvaisier et al, 2021). Further studies are however needed to verify the presence of fibrillar γ-tubulin assemblies in different model systems, determine their composition, structure and decipher their cellular function(s).…”
Section: γ-Tubulin Oligomers and Filamentsmentioning
confidence: 99%
“…Materials pGEX2T- TUBG1 (Addgene Plasmid # 171967) [6] pET21- TUBG1 (Addgene Plasmid # 101825) [13] E. coli DH5α (gives high protein yield from pGEX2T- TUBG1 plasmid; Thermo Fisher Scientific, cat. no.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Acentrosomal and centrosome-associated microtubules nucleate from the minus end on a complex formed of TUBG and various TUBG complex proteins, known as the TUBG ring complex [3] . TUBG is a ubiquitously expressed protein that forms a novel cytoskeleton/nucleoskeleton named the γ-tubulin meshwork [ [4] , [5] 6 ]. The meshwork can interact with various proteins, such as E2F1 [1] , lamin B1 [7] , Rad51 [8] , GCPs [3] , PCNA [6] , C53 [9] , and α- and β-tubulin dimers [ 2 , 3 ], and influences various cellular processes [ 4 , 10 , 11 ].…”
Section: Protocol Backgroundmentioning
confidence: 99%
See 1 more Smart Citation